Aplicación de una auditoría de gestión en la cooperativa de ahorro y crédito “Saquisilí” ltda., ubicada en la provincia de cotopaxi, cantón saquisilí, durante el período 2014 - Lema Chisag, Martha Cecilia (2015)
The audit is an analysis and diagnosis that is made to an entity with the goal to provide a decision-making advice. This research was conducted at “Saquisilí Ltda.” Savings and Credit Cooperative. No previously performed an audit of this type, which has caused the lack of implementing policies and pro The audit is an analysis and diagnosis that is made to an entity for the purpose of providing advice for decision-making. This research work was conducted at the credit union "Saquisilí" Ltda. No previously performed an audit of this type, which has caused the lack of implementing policies and procedures to successfully achieve the objectives. The Management Audit implementation was to determine compliance with the administrative and financial processes for which indicators of efficiency, effectiveness, economy, ethics, ecology and quality are applied….